'Precision Instruments for Dreaming': Anatomizing Keats in Pauline Stainer's The Wound-dresser's Dream. Issue 2 (July 2016) - John, Stefanie
Abstract : This essay examines allusions to Keats in the collection The Wound-dresser's Dream (1996) by the contemporary British poet Pauline Stainer. Drawing on the Keatsian notion of dreaming as a metaphor for poetic creativity and responding to Keats as both poet and physician, Stainer explores the interface between sense experience and imagination. As dreams seem to encode hidden meanings, so Stainer's writing evokes the impression that the textual riddles of her poems symbolize greater truths – while the nature of these truths is mostly left unclear. Through extensive use of allusion and surreal, sometimes opaque imagery she foregrounds the status of the poetic work as a linguistic construct. Yet she also maintains a Keatsian belief that poetry's ability to embrace uncertainties and mysteries affords it a unique grasp on actuality.